The rhetoric of Hindu India : language and urban nationalism - Basu, Manisha (Cambridge : Cambridge University Press, 2017)
This book examines the late twentieth-century rise of the urban, right-wing Hindu nationalist ideology known as metropolitan Hindutva. This ideology, the book assesses, aspires to be a pan-Indian, urban form that is home to the emerging, digitally enabled, technocratic middle classes of the nation. Through close analyses of the writings of a range of self-styled public intellectuals, from Arun Shourie and Swapan Dasgupta to Chetan Bhagat and Amish Tripathi, this book maps this new avatar of Hindutva. Finally, in analyzing the language of metropolitan Hindutva, it arrives at an emerging idea of India as part of what Amitav Ghosh has called a contemporary Anglophone empire. This is the first extended scholarly effort to theorize a politics of language in relation to the dangers of such an imperializing Hindutva.
Introductory matters : the strange case of secular India -- Time's victims in a second republic : new histories, new temporalities -- To make free and let die : the economics of metropolitan Hindutva -- A power over life and rebirth : V.D. Savarkar and the essentials of Hindutva -- Between death and redemption : Hindu India and its antique others -- The after-life of Indian writing in English : telematic managers, journalistic mantras.
Title from publisher's bibliographic system (viewed on 11 Aug 2017).
Keywords: Hindutva; Hinduism and politics -- India; Rhetoric -- Political aspects -- India; Nationalism -- Political aspects -- India; India -- Politics and government -- 1977-